Enhanced sensitivity of neutralizing antibody detection for different AAV serotypes using HeLa cells with overexpressed AAVR - Zheng, Zhaoyue; Ye, Jingya; Leng, Mi; Gan, Chunmei; Tang, Na; Li, Wei; Valencia, C. Alexander; Dong, Biao; Chow, Hoi Yee (Frontiers in Pharmacology, 2023)
A cell-based transduction inhibition assay (TI) is widely used in clinical trials to detect neutralizing antibody (NAb) titers against recombinant adeno-associated virus (rAAV), one of the most important criteria to exclude patients in gene therapy. Different cell lines are used in cell-based TI because the rAAV transduction efficiencies vary largely among serotypes. A cell line suitable for TI for most serotypes is highly desirable, especially for those with very low transduction efficiencies in vitro such as rAAV8 and rAAV9. Herein, we report an AAVR-HeLa, a stable cell line with overexpressed AAVR, a newly identified receptor for rAAVs, was established for cell-based TIs. The AAVR expression level in AAVR-HeLa cells was approximately 10-fold higher than in HeLa cells, and was stably transfected after twenty three passages. For all AAV serotypes (AAV1-10), except for AAV4, the transduction efficiencies increased significantly in AAVR-HeLa cells. It was demonstrated that the AAVR enhancement of transduction efficiency was only for rAAV and not for lentiviral and adenoviral vectors. According to the minimal multiplicity of infection (MOIs) for the assay, the NAb detection sensitivity increased at least 10 and 20 fold for AAV8 and AAV9, respectively. The seroprevalence of NAbs were investigated at the 1:30 level as a cutoff value using AAVR-HeLa cells. It was shown that the seropositive rate for AAV2 was 87% in serum samples from 99 adults, followed by lower seropositive rates for AAV5 (7%), AAV8 (7%) and AAV9 (1%). Venn diagram analysis showed the presence of cross-reactivity of NAbs to two or three serotypes in 13 samples (13.1%). However, no patient was found to possess NAbs for all the four serotypes. These results demonstrated that the AAVR-HeLa cell line may be utilized to detect the NAbs through cell-based TI assays for most of AAV serotypes.